Effects of ocean acidification on intestinal homeostasis and organismal performance in a marine bivalve: From microbial shifts to physiological suppression - Minggui Liu; Xiaoyu Guo; Lanfang Han; Yuanyuan Zhao; Chengjun Ge (Marine Pollution Bulletin, 2026)

Overcoming uranium re-dissociation in microbial electrolysis cells: Hydrogen-bond mediated reduction mechanisms in sulfate-reducing bacteria systems - Leyi Chen; Yuchen Yang; Kengqiang Zhong; Xing Lu; Haowen He; Xing Chen; Luoyi Han; Chengjun Guo; Meng Li; Lei Huang; Jia Yan; Diyun Chen; et al. (Chemical Engineering Journal, 2025)

Harnessing nanomaterial-driven electron transfer for enhanced uranium recovery and toxicity mitigation in bioelectrochemical systems - Meng Li; Leyi Chen; Kengqiang Zhong; Haowen He; Xing Chen; Xing Lu; Chengjun Guo; Luoyi Han; Ziyin Xia; Chenxi Li; Jingyi Wang; Wei Han; et al. (Bioresource Technology, 2025)

Estimation of Genetic Parameters for Hypoxia Tolerance in the Pacific Oyster, Crassostrea gigas - Mengmeng Xu; Ben Yang; Xiaojie Han; Deqi Sun; Chao Guo; Chengjun Zhi; Qi Li; Shikai Liu (Journal of Ocean University of China, 2025)

Autochthonous DOM governs the occurrence and methylation of mercury-containing nanoparticles in urban river water: An integrated study of field investigations and laboratory experiments - Jin Zhang; Pei Lei; Huan Zhong; Nan Zou; Martin Tsz-Ki Tsui; Carl P.J. Mitchell; Chengjun Li; Weiping Cai; Han Meng; Huan He; Fei Dang (Journal of Hazardous Materials, 2025)

Advances in sulfate-reducing bacteria-driven bioelectrolysis: mechanisms and applications in microbial electrolysis cell technology - Chenxi Li; Yuchen Xie; Jingyi Wang; Chengjun Guo; Luoyi Han; Ziyin Xia; Zijian Zhang; Junhe Wang; Meng Li; Wei Han; Lei Huang; Jia Yan; et al. (Environmental Research, 2025)

Genetic Basis of Low-Salinity Tolerance in the Pacific Oyster (Crassostrea gigas) as Revealed by Estimation of Genetic Parameters and Genome-Wide Association Study - Xiaojie Han; Ben Yang; Chao Guo; Mengmeng Xu; Deqi Sun; Chengjun Zhi; Qi Li; Shikai Liu (Marine Biotechnology, 2025)

Crystallization behavior of BOF slag during the cooling process towards leaching for CO2 sequestration - Xiaohui Mei; Qing Zhao; Chengzhi Han; Zengrui Wang; Yi Min; Chengjun Liu; Henrik Saxén; Ron Zevenhoven (Process Safety and Environmental Protection, 2024)

Occurrence and distribution of phycotoxins in the Antarctic Ocean - Jiale Tang; Xiuping He; Junhui Chen; Wei Cao; Tongzhu Han; Qinzeng Xu; Chengjun Sun (Marine Pollution Bulletin, 2024)

Au doped metal organic frameworks as di-functional photocatalysts for clearing organics in wastewater - Donglin Han; Juntao Niu; Yuchen Yang; Chengjun Huang; Wenguang Tan; XuanYi Zhang (Chemosphere, 2024)

Correction to: Weak transgenerational effects of ancestral nitrogen and phosphorus availabilities on offspring phenotypes in Arabidopsis thaliana - Zhengbing Yan; Di Tian; Wenxuan Han; Chengjun Ji; Xinghui Hou; Yalong Guo; Jingyun Fang (Journal of Plant Research, 2023)

Weak transgenerational effects of ancestral nitrogen and phosphorus availabilities on offspring phenotypes in Arabidopsis thaliana - Zhengbing Yan; Di Tian; Wenxuan Han; Chengjun Ji; Xinghui Hou; Yalong Guo; Jingyun Fang (Journal of Plant Research, 2023)

Intensified gas-phase hydrogenation of acetone to isopropanol catalyzed at metal-oxide interfacial sites - Kun Liu; Yongbin Sun; Jie Feng; Yang Liu; Jian Zhu; Chengjun Han; Changzhi Chen; Tianyi Bao; Xiaoqun Cao; Xiaomin Zhao; Yong Yang; Guofeng Zhao (Chemical Engineering Journal, 2023)

Comparison of sedimentary organic carbon loading in the Yap Trench and other marine environments - Dong Li; Jun Zhao; Chenggang Liu; Chengjun Sun; Jianfang Chen; Jianming Pan; Zhengbing Han; Ji Hu (Journal of Oceanology and Limnology, 2020)

Degradation potential and diversity of oil-degrading bacteria isolated from the sediments of the Jiaozhou Bay, China - Wei Gao; Xiangxing Gao; Tiezhu Mi; Bin Han; Yiran Zhang; Xinzi Li; Xiaofei Yin; Chengjun Sun; Qian Li; Zhisong Cui; Xiao Luan; Zhigang Yu; et al. (Acta Oceanologica Sinica, 2019)

Study on immobilization of marine oil-degrading bacteria by carrier of algae materials - Yiran Zhang; Wei Gao; Faxiang Lin; Bin Han; Changfei He; Qian Li; Xiangxing Gao; Zhisong Cui; Chengjun Sun; Li Zheng (World Journal of Microbiology and Biotechnology, 2018)

Lipid accumulation and CO2 utilization of two marine oil-rich microalgal strains in response to CO2 aeration - Shuai Wang; Li Zheng; Xiaotian Han; Baijuan Yang; Jingxi Li; Chengjun Sun (Acta Oceanologica Sinica, 2018)

Retraction Note to: Nucleolin Promotes TGF-β Signaling Initiation via TGF-β Receptor I in Glioblastoma - Shunzeng Lv; Jie Zhang; Mingzhi Han; Weiping Wang; Ya Zhang; Dongxiao Zhuang; Ranran Shi; Ruixiang Bian; Chengjun Yao (Journal of Molecular Neuroscience, 2017)

RETRACTED ARTICLE: Nucleolin Promotes TGF-β Signaling Initiation via TGF-β Receptor I in Glioblastoma - Shunzeng Lv; Jie Zhang; Mingzhi Han; Weiping Wang; Ya Zhang; Dongxiao Zhuang; Ranran Shi; Ruixiang Bian; Chengjun Yao (Journal of Molecular Neuroscience, 2015)

Significant soil acidification across northern China's grasslands during 1980s–2000s - Yuanhe Yang; Chengjun Ji; Wenhong Ma; Shifeng Wang; Shaopeng Wang; Wenxuan Han; Anwar Mohammat; David Robinson; Pete Smith (Global Change Biology, 2012)
Anthropogenic acid deposition may lead to soil acidification, with soil buffering capacity regulating the magnitude of any soil pH change. However, little evidence is available from large‐scale observations. Here, we evaluated changes in soil pH across northern China's grasslands over the last two decades using soil profiles obtained from China's Second National Soil Inventory during the 1980s and a more recent regional soil survey during 2001–2005. A transect from the central‐southern Tibetan Plateau to the eastern Inner Mongolian Plateau, where Kriging interpolation provided robust predictions of the spatial distribution of soil pH , was then selected to examine pH changes during the survey period. Our results showed that soil pH in the surface layer had declined significantly over the last two decades, with an overall decrease of 0.63 units (95% confidence interval = 0.54–0.73 units). The decline of soil pH was observed in both alpine grasslands on the Tibetan Plateau and temperate grasslands on the Inner Mongolian Plateau. Soil pH decreased more intensively in low soil carbonate regions, while changes of soil pH showed no significant associations with soil cation exchange capacity. These results suggest that grassland soils across northern China have experienced significant acidification from the 1980s to 2000s, with soil carbonates buffering the increase in soil acidity. The buffering process may induce a large loss of carbon from soil carbonates and thus alter the carbon balance in these globally important ecosystems.

Comparative analyses of leaf anatomy of dicotyledonous species in Tibetan and Inner Mongolian grasslands - JianJing Ma; ChengJun Ji; Mei Han; TingFang Zhang; XueDong Yan; Dong Hu; Hui Zeng; JinSheng He (Science China Life Sciences, 2012)

Antidepressant-like effects of PDE4 inhibitors mediated by the high-affinity rolipram binding state (HARBS) of the phosphodiesterase-4 enzyme (PDE4) in rats - Han-Ting Zhang; Yu Zhao; Ying Huang; Chengjun Deng; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2006)

Effects of the novel PDE4 inhibitors MEM1018 and MEM1091 on memory in the radial-arm maze and inhibitory avoidance tests in rats - Han-Ting Zhang; Ying Huang; Neesha U. Suvarna; Chengjun Deng; Alicia M. Crissman; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2005)